Caracterização Textural dos Sedimentos de Fundo do Lago Guaíba (sul do Brasil) e sua Importância em Diagnósticos Ambientais - LAYBAUER, LUCIANO; BIDONE, EDISON DAUSACKER (Pesquisas em Geociências, 2001)
This work detaches the importance of understanding the sedimentary dynamics in environmental researches. One hundred eighty seven bottom sediment samples from Guaíba Lake were collected in 1998. These samples were analyzed for texture and organic matter content. Those physical parameters associated to the lake’s morfodynamics show preferential sites to accumulate fine sediments and organic matter; those are potential geochemical carriers of pollutants. Four textural fields (A: 0-10%, B: 10-50%, C: 50-90% and D: 90-100%) based on the mud percentage (fraction <63µm) of the sediments were defined. They indicate a growing potential of pollutant sorption. Environmental assessment should prioritize sampling of fields C, and especially D, to the detriment of fields A and B. the textural map based on this approach, shows the division of Guaíba Lake in three great cells of fine sediments called, North cell, Central cell and South cell. Future environmental researches carry on the Guaíba Lake can use this tool to orient sediment sampling.